Diagnostika hitrosti sprinterskega teka z laserskim merilnikom LDM-301 - Planjšek, Peter (Šport (Ljubljana), 2013)
The development of modern sport is closely linked to the invention of new technological, expert, scientific, research and organisational methods in the training process. Today, a top sport performance can no longer be generated merely through experience, intuition and other random factors. The procedures and decisions related to sports training must be rational and as efficient as possible. However, coaches need high quality information to be able to take effective decisions. In sprint training it is impossible to acquire high quality information about a sprinter's form and the efficiency of the training without complex integrated biomechanical methods. The Laboratory for Motion Control and the Laboratory of Biomechanics have developed a completely new method for diagnosing the dynamics of sprint speed. The laser distance meter enables key time parameters of speed to be identified in individual sprint zones.
Keywords: athletics; atletika; hitrost; laserski merilniki; LAVEG system; measurement of speed; merjenje hitrosti; sistem LAVEG; sport; sprint; šport; športna diagnostika